ETIOLOGY AND CLINICAL SPECTRUM OF ANTERIOR UVEITIS IN A TERTIARY EYE CARE HOSPITAL FROM EASTERN INDIA: A PROSPECTIVE INTERVENTIONAL STUDY - MISRA, ANITA; CHAUDHURY, PRANATI; MOHANTY, SUBHRAJYOTI; SAHOO, SASMITA; JENA, BICHISMITA; BADWAL, KALPANA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to study the etiology, clinical spectrum, management, and outcome of anterior uveitis in a tertiary eye care center in Eastern India and compares it with the data of other published reports. Methods: This study was a prospective interventional clinical research performed on all (new and old) anterior uveitis patients visiting our ophthalmology OPD for treatment between January 2020 and December 2022. A thorough history, clinical examination, and investigation procedures were performed to diagnose the exact etiology and clinical characteristics of anterior uveitis. After treatment, cases were followed up for 6 months. Results: Total cases of uveitis seen were 286, out of which anterior uveitis was the most common category with 150 cases (52%) which constituted the study population. Male patients were 71% whereas females were 29%. 61% of cases were in the age group of 20–40 years. 60% of cases were acute, 27% in chronic, whereas 13% were in the recurrent anterior uveitis stage. It was unilateral in 74% of cases. 72% of the cases were clinically nongranulomatous type. Idiopathic etiology was significantly seen in 62% of cases. For identifiable diseases, infectious cause was (16%), non-infectious (12%), and traumatic cause (10%). Infections of which the chief cause were tuberculosis (10%), viral (04%), and leprosy (02%), while in the non-infectious category of uveitis spondyloarthropathy (08%), lens-induced uveitis (04%) were the most common etiology. Before treatment vision in 15% of cases was 6/12 or better, which improved after treatment to 6/12 or better in 62% of cases. 34% of the patients had no residual complications after treatment, whereas the most common complication was persistent posterior synechia in 23% and cataract in 16% of cases. Conclusion: The cause in majority of the cases of anterior uveitis remained idiopathic. However, prompt diagnosis appropriate and adequate treatment, and follow-up could restore good vision without significant symptoms, sequelae, or ocular morbidity in majority of cases.